Instructor's manual to accompany cuisine and culture : - Civitello, Linda (John Wiley & Sons, Inc, 2008)
Its purpose is to make your life easier: to further emphasize, organize, and explain information in the text and to help you plan lessons, give tests and learn even more about food history through links to web site.